Cognitive symmetry-asymmetry and socio-affective affinity in the collaborative comprehension of frequency tables - Castellaro, Mariano (2019)
Objectives: the effects of competence symmetry-asymmetry and socio-affective affinity on the collaborative interaction to understand a frequency table were analyzed. Method: the participants were distributed in symmetric and asymmetric dyads taking into account the similarities and differences of their specific competences, and if they had or not reciprocal socio-affective affinity. Ninety (90) students (45 dyads) attending the sixth and seventh grades of primary school (age, M = 12.3, SD = .5), who were screened using a non-probability method, participated in the study. Each dyad answered 12 multiple-choice questions, each of which evaluated one aspect of the table comprehension. The collaborative interaction between the participants was analyzed from a three-hierarchical-level category system. Results: socioaffective affinity has influence on cognitive asymmetry. It is associated with a lower imbalance of peers’ contributions related to the resolution of the task. In contrast, in competition symmetry, socio-affective affinity was associated with slightest variations. Conclusions: the findings are discussed in terms of a situated or contextualizing perspective of the socio-cognitive event which aims to overcome the traditional epistemic conception.